Development and validation of Islamic Governance Examination tool in healthcare settings. Issue 1 (29th November 2019) - Abdul Rahman, Hanif; Abdul Aziz, Amin; Ibrahim, Muhamad Adib; Suhaili, Noor-Arpah; Daud, Ahmad Zahid; Naing, Lin
Abstract : Purpose: The purpose of this paper is to develop and validate the Islamic Governance Examination tool (IGET) in applicability to the healthcare setting. Design/methodology/approach: A cross-sectional study using IGET, developed by a panel of expert and extensive literature, which measures Islamic governance (IG) domains – Tauhid, Juristic, Values and Culture. Health and allied health professionals from the largest hospital in Brunei were recruited to establish validity and reliability of the instrument. Structural equation modelling (SEM) was applied to explore the relationship of the IG domains. Findings: Content validity and construct validity were established with good internal consistency reliability (Cronbach's α ranged 0.835–0.953). SEM supports the conceptual model and demonstrated potential to improve quality of health services. By articulating internal and organisational processes put in place for compatibility of Muslim patients and accommodating incumbent form of healthcare governance. Originality/value: To the authors' knowledge, this is the first study developing, validating and exploring IG components in healthcare setting. Usage of IGET should be cross-validated in different disciplines and settings before application. Nonetheless, IG as a whole need to be developed further to create healthcare environment compatible for Muslim patients and complement current health services to improve health service quality for everyone.